Pro serverless data handling with Microsoft Azure : architecting ETL and data-driven applications in the cloud - Kettner, Benjamin; Geisler, Frank (Apress, 2022)
Design and build architectures on the Microsoft Azure platform specifically for data-driven and ETL applications. Modern cloud architectures rely on serverless components more than ever, and this book helps you identify those components of data-driven or ETL applications that can be tackled using the technologies available on the Azure platform. The book shows you which Azure components are best suited to form a strong foundation for data-driven applications in the Microsoft Azure Cloud. If you are a solution architect or a decision maker, the conceptual aspects of this book will help you gain a deeper understanding of the underlying technology and its capabilities. You will understand how to develop using Azure Functions, Azure Data Factory, Logic Apps, and to employ serverless databases in your application to achieve the best scalability and design. If you are a developer, you will benefit from the hands-on approach used throughout this book. Many practical examples and architectures applied in real-world projects will be valuable to you on your path to serverless success.